The roles of environmental collective efficacy and allocentrism on green car purchase intention - Lim, Yi Jin (2020)
The deteriorating environmental quality and low green car sales in Malaysia highlight the imperative need to explore the role of consumers and the driving factors that influence their green car purchase intention in order to increase the demand for green cars. Therefore, based on the social cognitive theory, this study assessed the relationships of external environmental factors (social influence, green labelled, and economic incentives) and personal factors (environmental attitude, environmental knowledge, and past green purchase behavior) with green car purchase intention. Furthermore, the mediating impact of environmental collective efficacy and the moderating impact of allocentrism on the aforementioned relationships were also investigated. I This study employed multi-stage sampling method which included stratified sampling and systematic mall intercept strategies. This study successfully surveyed 417 consumers-aged 18 years and above - who visited the showrooms of Honda, Toyota, and Nisan in Kuala Lumpur and Penang. The results of the structural model supported 7 out of 13 direct hypothesized paths that involved the relationships of green labeling, economic incentives, environmental attitude, environmental collective efficacy, and green car purchase intention as well as the relationships of economic incentives, environmental attitude, environmental knowledge, and environmental collective efficacy. Additionally, the results demonstrated the mediating impact of environmental collective efficacy between economic incentives, environmental attitude, environmental knowledge and green car purchase intention. The results further revealed a significant relationship between social influence and green car purchase intention at low allocentric level, which demonstrated the moderating impact of allocentrism. The results of this study provide important insights to green marketing researchers, marketers and policy makers. Finally, the implications and limitations of the study as well as the suggestion for future research were discussed.